The Image of the Nobles in the Writings of the Grand Duchy of Lithuania - Kuolys, Darius (Senoji Lietuvos literatūra, 2019)
Based on sixteenth-eighteenth-century texts (the nobles’ letters, wills, panegyric and occasional literature dedicated to them, dedications in historical, philosophical, legal, and religious books), this paper analyses the image of the nobles as it arises in the writings of the Grand Duchy of Lithuania. The article interprets the meanings of this image and discusses the emerging social and political roles of the nobles.From the sixteenth century, literature closely associated the nobles with the republic of the Grand Duchy of Lithuania: the political community of the state of Lithuania, its rights, freedoms, and sovereignty. In his letter to Mikalojus Radvila Rudasis of 1551, Mikalojus Radvila Juodasis vividly described a noble’s connection with his republic: ‘[we] are appointed the Guardians in the Grand Duchy of Lithuania’.Not the rulers but the nobles are shown as the authors of the Statutes of Lithuania and the custodians of the history of Lithuania. It was for the nobles – the Sapiega and the Radvila as the protectors of the nation’s law – that the Third Statute of Lithuania was regularly reprinted between the sixteenth and the eighteenth centuries. It is to them that Albertas Kojalavičius-Vijūkas, the greatest seventeenth-century historian of the Grand Duchy of Lithuania, entrusts the history of Lithuania in the forewords and commits them to take care of the continuity of the Lithuanian nation. The whole history of Lithuania is publicly identified with the history of the Radvila family. Occasional literature of the Grand Duchy of Lithuania established and consolidated, in public life, an ideal image of a noble as ‘the father of the homeland’, ‘the father of the nation’, and a pillar of the homeland. In many instances, this image rests on the tradition of the Roman Republic, and the concept of the virtuous citizen and the ‘good man’ (vir bonus) defended by its authors. Having nurtured his eloquence and mastered the secrets of rhetoric, the noble is capable of ruling a free nation not by violence but by persuasion.In the writings of Lithuania, the noble arises as an embodiment and guardian of, and a witness to the values and ideas relevant to the Republic. His exceptional virtues include loyalty and service to the Republic and sacrifice of his personal prosperity for the common good. It is these moral imperatives that the nobles pass over to their progeny in their testaments. Occasional literature extolls the Radvila, the Chodkevičius, the Sapiega, and other nobles as the custodians of the citizens’ rights and freedoms. A noble’s honourable conduct is linked to the moral and social order in the state.In the culture of the Grand Duchy of Lithuania, the nobles seem to assimilate the symbolic roles of the ancient grand dukes and their obligation to safeguard the fate of the state and justice. With their inherited, nurtured, and embodied virtues, they give their fellow citizens an example of ethical behaviour and protect moral order in the state. Like the grand dukes of Lithuania, the nobles are derived from the legendary Roman princes. They arise as the successors to the deeds of the ancient Lithuanian rulers Gediminas, Algirdas, and Vytautas. Rooted in the mythical and historical past of the nation, the families of the nobles impart the experience of temporal stability, ‘eternity’, and existential sustainability to the entire political community of Lithuania and the whole Republic. A noble that unites the political nation seems to compensate for the rallying image of the ruler in the culture of the Grand Duchy of Lithuania. It is not the ruler but the noble that becomes the symbol of Lithuania’s sovereignty. In literature, he is depicted as protecting the Republic of the Grand Duchy of Lithuania more consistently than the ruler, and sometimes even against the ruler’s will.The ideal image of the noble created and developed in the writings of the sixteenth-seventeenth centuries retains its relevance in the culture of the Age of Enlightenment. This image became an essential part of the political identity of the Grand Duchy of Lithuania.
Keywords: the nobles; lords; fathers of the homeland; image; virtues; republic; Radvila; Chodkevičius; Sapiega